A Comprehensive Analysis of the Factors Influencing Absenteeism among Medical Students at the University of Zawia, Libya - Zinab Elfituri; Bushra Gamoudi; Adel Kerfa; Shahrazad Gazeti; Rodaba Bitrou; Hana Alazraq; Huria Dardar; Ali Alahrash; Suliman Essa; Reemah Almadah; et al. (AlQalam Journal of Medical and Applied Sciences, 2024)
Attendance of undergraduate medical students is crucial for their medical education, but absenteeism is a growing problem globally due to academic and personal challenges. This study at the University of Zawia surveyed 302 undergraduate medical students, primarily female, to understand the factors influencing their attendance. The study found that, external factors like traffic congestion and high costs of private transportation impacted attendance, while pedagogical factors like preferring home-based learning and dissatisfaction with teaching methods were significant. Social factors like peer influence were less influential, suggesting commitment to the field. Institutional factors like inadequate classroom resources, poor infrastructure, scheduling, and security were major concerns. The college’s response to absenteeism was moderate, suggesting that institutional issues may be less critical. The study underscores the complex interplay of external, academic, and personal factors affecting student participation in medical education. Factors like traffic congestion, high costs of transportation, and inadequate infrastructure significantly hinder attendance, while dissatisfaction with traditional teaching methods and the belief that non-attendance does not affect grades are notable academic factors. Faculty-related issues, such as unclear explanations and ineffective teaching methods, greatly influence attendance decisions. Study recommendations include improving public transportation, updating teaching tools and classroom facilities, and enhancing teaching quality and engagement to address the complex interplay of factors affecting student attendance in medical education programs. يُعد حضور طلاب الطب البكالوريوس أمرًا بالغ الأهمية لتعليمهم الطبي، لكن الغياب مشكلة متزايدة على مستوى العالم بسبب التحديات الأكاديمية والشخصية. أجريت هذه الدراسة في جامعة الزاوية على 302 طالب وطالبة طب بكالوريوس، غالبيتهم من الإناث، لفهم العوامل المؤثرة على حضورهم. وجدت الدراسة أن العوامل الخارجية مثل الازدحام المروري والتكاليف العالية للمواصلات الخاصة تؤثر على الحضور، في حين أن العوامل التربوية مثل تفضيل التعلم المنزلي وعدم الرضا عن طرق التدريس كانت ذات أهمية. كانت العوامل الاجتماعية مثل تأثير الأقران أقل تأثيراً، مما يشير إلى الالتزام بالمجال. كانت العوامل المؤسسية مثل عدم كفاية الموارد الصفية والبنية التحتية السيئة والجدولة والأمن من الشواغل الرئيسية. كان استجابة الكلية للغياب متوسطة، مما يشير إلى أن القضايا المؤسسية قد تكون أقل أهمية. تؤكد الدراسة على التفاعل المعقد بين العوامل الخارجية والأكاديمية والشخصية التي تؤثر على مشاركة الطلاب في التعليم الطبي. عوامل مثل الازدحام المروري والتكاليف العالية للمواصلات والبنية التحتية غير الكافية تعيق الحضور بشكل كبير، في حين أن عدم الرضا عن طرق التدريس التقليدية والمعتقد بأن الغياب لا يؤثر على الدرجات هي عوامل أكاديمية بارزة. تؤثر القضايا المتعلقة بالهيئة التدريسية، مثل الشرح غير الواضح وطرق التدريس غير الفعالة، بشكل كبير على قرارات الحضور. تشمل توصيات الدراسة تحسين وسائل النقل العام وتحديث أدوات التدريس ومرافق الفصول الدراسية وتعزيز جودة التدريس والمشاركة لمعالجة التفاعل المعقد للعوامل المؤثرة على حضور الطلاب في برامج التعليم الطبي